2018
DOI: 10.3389/fnut.2018.00011
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Ketogenic Diet As Treatment for Primary Aggressive Brain Cancer: Challenges and Lessons Learned

Abstract: Survival of glioblastoma multiforme (GBM) with the current recommended treatment is poor. Reported median survivals are approximately 8–15 months. Based on recent publications from animal models, combining cancer drugs, radiation, and diet-metabolic treatments may be a new route to better survivals. To investigate this possibility, we have begun a clinical trial that has enrolled 15 subjects using a ketogenic diet (KD) as an addition to current standard treatments that include surgery, radiation therapy, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 38 publications
(35 reference statements)
1
35
0
1
Order By: Relevance
“…While preclinical data suggests great promise for KD treatment of GBM, few clinical studies have been done [24][25][26][27][28][29][30][31]. Part of the reason is the difficulty of doing KD.…”
Section: Feasibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…While preclinical data suggests great promise for KD treatment of GBM, few clinical studies have been done [24][25][26][27][28][29][30][31]. Part of the reason is the difficulty of doing KD.…”
Section: Feasibilitymentioning
confidence: 99%
“…KD poses three main challenges: lack of palatability, the complicated nature of meal preparation, and lack of standardization. Of the four published KD GBM studies with > 2 patients, three concluded that KD cannot be tolerated for more than 6-12 weeks [26][27][28], and that the maximally tolerated diet is 3:1 with 20 g CH. In a German study of restrictive calorie ketogenic diet in end-stage malignant tumors only 5/16 subjects completed the 3-month treatment period [32].…”
Section: Feasibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Diet adherence and compliance remain significant barriers to successful implementation and an adequate assessment of KD efficacy. Common methodologies to assess and document KD adherence in adults beyond patient self-report include frequent measurements of serum β-hydroxybutyrate or urine acetoacetate concentrations during the first few weeks on the diet and/or collection of dietary food records [57,121,128]. As examples, daily urine ketone assessments are traditionally used in adults with epilepsy during MAD initiation until moderate to large levels of ketosis are reached and serum ketone assessments using drops of blood from a finger stick have been used to guide short-term KD therapy in patients with GBM [53,128].…”
Section: Management Of Adverse Effects and Poor Compliance In Adultsmentioning
confidence: 99%